The Development of an Ethernet-based Portable Embedded Isolated ECG System - AlMejrad, A. S. (Engineering, Technology & Applied Science Research, 2021)
Patient monitoring is an important issue in the medical field, requiring planning, effort, and time. One of the challenges that physicians, nurses, paramedics, and emergency medical technicians face is the shortage of specialized medical equipment and staff with the ability to measure, display, store, and transmit the vital signs of patients for remote diagnosis under critical conditions. Therefore, and based on our evaluation for such needs, our main research objective was to develop a new system to enable these professionals to perform such monitoring functions with a higher level of safety, performance, and time effectiveness with reduced cost. An advanced, integrated, effortless, and portable system was developed, which is capable to measure, monitor, display, store, and transmit data related to the Electrocardiography (ECG) signal along with its derivatives, such as the heart rate using a hybrid system that combines hardware and software.